Global Bibliometric Mapping of Zakat Marketing: Trends, Actors, and Digital Transformation (2000–2025) - Khodijah, Siti; Irfan Abdurahman, Ade (Educational Researcher Journal, 2025)
This study aims to map the intellectual landscape and global evolution of scientific literature on zakat marketing from 2000 to 2025, identifying the trends, conceptual structures, key actors, and future directions of this rapidly growing research field. Using a bibliometric analysis method on data extracted from the Scopus database, quantitative analysis was conducted through performance analysis and science mapping. The results show exponential publication growth after 2017, driven by digital technology adoption accelerated by the COVID-19 pandemic, with a research landscape geographically dominated by a collaboration axis between Indonesia and Malaysia. Key research themes identified are the integration of zakat with Islamic banking to achieve economic growth, and the significant role of digital transformation through fintech, especially in the context of the COVID-19 pandemic. In conclusion, zakat marketing research has evolved from a limited niche into a dynamic and interdisciplinary field of strategic management, signifying a paradigm shift from normative studies towards a discipline integrated within the broader Islamic finance discourse. This study provides a comprehensive roadmap for practitioners and academics to optimize the potential of Islamic philanthropy in the digital age.